Applying venn diagram to present bloom’s cognitive level of students of a physics learning about light refraction using developed independent lab work module and PhET simulation “bending light” - Nurul H. Astuti; Debora Natalia Sudjito; Diane Noviandini (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2018)
Evaluation shows the effectiveness of teaching and learning of a class. Mostly teachers provide evaluation in low cognitive level so students are able to achieve the minimum passing grade. Whereas a good evaluation should use Bloom’s Taxonomy as a basis for classifying student’s cognitive level. It leads teacher to provide a learning that facilitates student’s achievement of high cognitive level, including using independent lab work module. Teachers also typically provide a global report evaluation, i.e. providing the final score only, without presenting the distribution of students’ cognitive level. For this purpose, Venn Diagram is used to show the distribution of students’ cognitive level based on Bloom Taxonomy. This research aimed to present the distribution of students’ Bloom cognitive level using Venn Diagram and to investigate whether the development of independent lab work module about light refraction using PhET simulation “Bending Light“ can make students achieve the cognitive levels of knowing, understanding, applying, and analyzing. The obtained data was analyzed using qualitative descriptive method. The respondents were 17 freshmen of Physics Education and Physics Students of UKSW Batch 2016. The post-test showed that all students achieved higher cognitive levels. Thus, the developed independent lab work module was able to improve students’ cognitive level. Venn Diagram could also simplify the presentation of the distribution of students’ Bloom cognitive level for teachers.